2014
DOI: 10.1016/j.yexcr.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Getting more for your marrow: Boosting hematopoietic stem cell numbers with PGE2

Abstract: Throughout the lifetime of an individual, hematopoietic stem cells (HSCs) self-renew and differentiate into lineages that include erythrocytes, platelets and all immune cells. HSC transplantation offers a potentially curative treatment for a number of hematopoietic and non-hematopoietic malignancies as well as immune and genetic disorders. Limited availability of immune-matched donors reduces the viable options for many patients in need of HSC transplantation, particularly those of diverse racial and ethnic ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 39 publications
1
34
0
1
Order By: Relevance
“…The ability of PGE2 to promote hematopoiesis has been documented by two types of experiments: (i) ex vivo treatment of hematopoietic stem cells with dmPGE2 improves stem cell engraftment and consequent survival of mice, and (ii) administration of PGE2 or dmPGE2 to sub-lethally irradiated mice accelerates hematopoietic recovery and increases numbers of the short-term subtype of hematopoietic stem cells (11, 1317, 2427). Previous work also revealed that dmPGE2-treated cells have increased levels of cyclic AMP, increased expression of CXCR4 and survivin, decreased apoptosis, and increased homing to the bone marrow stem cell niche (11, 1416, 24, 25, 27).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of PGE2 to promote hematopoiesis has been documented by two types of experiments: (i) ex vivo treatment of hematopoietic stem cells with dmPGE2 improves stem cell engraftment and consequent survival of mice, and (ii) administration of PGE2 or dmPGE2 to sub-lethally irradiated mice accelerates hematopoietic recovery and increases numbers of the short-term subtype of hematopoietic stem cells (11, 1317, 2427). Previous work also revealed that dmPGE2-treated cells have increased levels of cyclic AMP, increased expression of CXCR4 and survivin, decreased apoptosis, and increased homing to the bone marrow stem cell niche (11, 1416, 24, 25, 27).…”
Section: Resultsmentioning
confidence: 99%
“…Another area of active development is to improve engraftment of transplanted HSPCs through the use of homing promoting effectors (reviewed in [117,118] inhibitor CHIR-911 [123], the histone deacetylase inhibitor valproic acid [124][125][126], the glycosaminoglycans hyaluronic acid [127], and complement molecule C3a [128,129] to name a few.…”
Section: Molecules That Promote Engraftment Through Improved Homingmentioning
confidence: 99%
“…Ex vivo treatment of one of the two UCB units using prostaglandin E2 (dmPGE2) aimed at enhancing HSC homing by upregulating CXCR4 and HSC survival (FT1050; ProHema) [102][103][104][105][106].…”
Section: IIImentioning
confidence: 99%
“…In a subsequent similar clinical trial, but for which the dmPGE2 treatment of the UCB cells was irst optimized, improved time to neutrophil recovery (median 1 .5 days) was observed when compared with historical controls (21 days) and with the dmPGE2 primed UCB unit engrafting in over 80% of the patients. This has preceded to a Phase II clinical trial [106], and recent studies suggest that dmPGE2 may modulate Wnt signaling in UCB T cells and enhance immune reconstitution postransplant [103]. The efects of dmPGE2 in patients undergoing myeloablative conditioning are unknown.…”
Section: IVmentioning
confidence: 99%